2019
DOI: 10.3390/nano9091284
|View full text |Cite
|
Sign up to set email alerts
|

Effective Oxygen Reduction Reaction Performance of FeCo Alloys In Situ Anchored on Nitrogen-Doped Carbon by the Microwave-Assistant Carbon Bath Method and Subsequent Plasma Etching

Abstract: Electrocatalysts with strong stability and high electrocatalytic activity have received increasing interest for oxygen reduction reactions (ORRs) in the cathodes of energy storage and conversion devices, such as fuel cells and metal-air batteries. However, there are still several bottleneck problems concerning stability, efficiency, and cost, which prevent the development of ORR catalysts. Herein, we prepared bimetal FeCo alloy nanoparticles wrapped in Nitrogen (N)-doped graphitic carbon, using Co-Fe Prussian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…25,27 Recently, FeCo alloy@N-doped graphite carbon was synthesized by using a combination of microwave-assisted carbon bath and dielectric barrier discharge plasma treatment. 28 The results indicated that the co-existence of Fe/Co N sites and core-shell structure could significantly promote the ORR. Nevertheless, the aforementioned catalysts were typically synthesized by using complicated heat treatment of transition metals with macrocyclic nitrogen complexes, [29][30][31][32] Prussian blue analogs 33,34 and ionic liquids [35][36][37] which could be too expensive to be practically utilized.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…25,27 Recently, FeCo alloy@N-doped graphite carbon was synthesized by using a combination of microwave-assisted carbon bath and dielectric barrier discharge plasma treatment. 28 The results indicated that the co-existence of Fe/Co N sites and core-shell structure could significantly promote the ORR. Nevertheless, the aforementioned catalysts were typically synthesized by using complicated heat treatment of transition metals with macrocyclic nitrogen complexes, [29][30][31][32] Prussian blue analogs 33,34 and ionic liquids [35][36][37] which could be too expensive to be practically utilized.…”
Section: Introductionmentioning
confidence: 95%
“…Moreover, the N‐coordinated FeCo alloys electrocatalysts could further enhance the ORR activity and long‐term durability in both acid and alkaline solution 25,27 . Recently, FeCo alloy@N‐doped graphite carbon was synthesized by using a combination of microwave‐assisted carbon bath and dielectric barrier discharge plasma treatment 28 . The results indicated that the co‐existence of Fe/CoN sites and core‐shell structure could significantly promote the ORR.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon-based materials have more advantages than traditional materials, such as low costs, various structures, and good electrical and thermal conductivity. The excellent catalytic performance can be obtained by tailoring carbon-based materials with specific sizes, doping types, contents, morphologies and structures, promoting active site exposure, increasing the transport of reaction-related substances, and enhancing the transfer of electrons throughout the electrode [120,121]. At the same time, more defects become the active sites of the electrocatalyst after heteroatom doping.…”
Section: Carbon Based Electrocatalystsmentioning
confidence: 99%
“…These efforts resulted in promising ORR catalysts which can be broadly classified into three categories: non-PGM metal catalysts [2], metal-free catalysts especially hetero-atom doped carbons [3] and hybrids of non-PGM catalysts with carbon nano-structures [4]. Amongst these three, the third type of carbon-metal hybrids which consists of nano sized non-PGM metal compounds of iron [5], cobalt [6], manganese [7] etc. embedded/dispersed/anchored on nano scaled carbons such as graphene [8], carbon nanotubes [9] and carbon nanofibers [10] have rapidly evolved as attractive alternatives to PGM based ORR electro-catalysts.…”
Section: Introductionmentioning
confidence: 99%